Little children [videorecording (DVD)] - Field, Todd; Winslet, Kate; Wilson, Patrick, 1973-; Connelly, Jennifer; Perrotta, Tom, 1961- (New Line Home Entertainment : Distributed by Warner Home Video, 2007)
Sarah Pierce is a new stay at home mom struggling with the solitude of her new role. Spending every moment with a three year old tests the patience of the one-time English scholar. One day, at a local playground, she interacts with a group of moms and the differences are clear. They embrace motherhood and seem to relish all that their new role brings. One day, Brad, a stay at home dad brings his son to the playground. Sarah is amazed to find these mom have never talked to Brad and one of the women bets Sarah five dollars that she won't get his phone number. Sarah not only gets his phone number, but lets him in on the joke and they hug and kiss. Emasculated by his wife, Kathy, Brad becomes slightly obsessed with finding ways to demonstrate he can still produce testosterone. Soon, Sarah and Brad start a passionate affair. At the same time, their quiet suburban community deals with Ronnie, a convicted pedophile who has just been released from prison. He returns to his mother's home and she helps him endure the constant taunts of an overzealous neighbor. These lives intersect in surprising and potentially dangerous ways.